PERFORATED DUODENAL ULCER ASSOCIATED WITH SITUS INVERSUS AND DEXTROCARDIA - Ibrahim, Mumtaz; HUssain, Dildar; Waheed, Seema; Tahir, Raazia; Haider, Ghulam; Ali, Nauyan; Sarfraz, Shahid Latif (Journal of Ayub Medical College Abbottabad, 2016)
A 32 years old gentleman, presented in emergency department, with complaints of sudden onset of severe upper abdominal pain, associated with nausea and vomiting. He was a known case of acid peptic disease. His abdominal examination showed signs of peritonitis. X-ray chest showed pneumoperitoneum, with dextrocardia. Ultrasound showed situs inversus. Exploration confirmed the diagnosis of perforated ulcer and situs inversus. Grahm’s patch repair of perforation was done. His postoperative recovery was smooth.